2014
DOI: 10.1002/ana.24303
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive genomic approach for neuromuscular diseases gives a high diagnostic yield

Abstract: Our results strongly indicate that for molecular diagnosis of heterogeneous disorders such as NMDs, targeted panel testing has the highest clinical yield and should therefore be the preferred first-tier approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 31 publications
4
127
3
1
Order By: Relevance
“…Our LGMD panel diagnostic yield (27%) is smaller than that of our previous NMD panel (46%) since previously yield was for all NMDs, not just for LGMD, and the cohort was much smaller (81 patients) 17. Identification of pathogenic variants in dominant LGMD genes DNAJB6 , MYOT , and CAV3, but not in the TNPO3 gene indicates a higher prevalence of dominant LGMD‐subtypes‐1E,1A,1C, respectively, and the rarity of LGMD‐1F.…”
Section: Discussioncontrasting
confidence: 57%
“…Our LGMD panel diagnostic yield (27%) is smaller than that of our previous NMD panel (46%) since previously yield was for all NMDs, not just for LGMD, and the cohort was much smaller (81 patients) 17. Identification of pathogenic variants in dominant LGMD genes DNAJB6 , MYOT , and CAV3, but not in the TNPO3 gene indicates a higher prevalence of dominant LGMD‐subtypes‐1E,1A,1C, respectively, and the rarity of LGMD‐1F.…”
Section: Discussioncontrasting
confidence: 57%
“…There is less uniform coverage in wholeexome sequencing, and up to 10% of the region of interest may not be adequately covered. 16 Thus, although whole exome and wholegenome sequencing are amen able to novel gene discovery, the time frame required for characterization and validation of a novel gene is often too long to be of practical help for sick neonates.…”
Section: Discussionmentioning
confidence: 99%
“…A previously published neuromuscular cohort study found a higher diagnosis rate for a 41-gene panel compared with clinician-requested single gene testing (46% vs 15-19%). 24 Coverage of the panel approach, with targeted capture of neuromuscular disease genes and Sanger fill-in of low-coverage exons, was better than WES, with 11 to 18% of pathogenic variants potentially missed by WES. 24 Challenges with coverage apply to both NGS panels and WES, and are frequently gene specific, with GC-rich, repeat regions, and exon 1 often poorly covered.…”
Section: Discussionmentioning
confidence: 99%
“…24 Coverage of the panel approach, with targeted capture of neuromuscular disease genes and Sanger fill-in of low-coverage exons, was better than WES, with 11 to 18% of pathogenic variants potentially missed by WES. 24 Challenges with coverage apply to both NGS panels and WES, and are frequently gene specific, with GC-rich, repeat regions, and exon 1 often poorly covered. FKRP is a good example, with up to 40% of the gene not well covered.…”
Section: Discussionmentioning
confidence: 99%